Effect of a Practice-wide Anti-TNF Proactive Therapeutic Drug Monitoring Program on Outcomes in Pediatric Patients with Inflammatory Bowel Disease. Issue 4 (25th May 2020) - Lyles, John L; Mulgund, Aditi A; Bauman, Laura E; Su, Weizhe; Fei, Lin; Chona, Deepika L; Sharma, Puneet; Etter, Renee K; Hellmann, Jennifer; Denson, Lee A; Minar, Phillip; Dykes, Dana M; et al.
Abstract: Background: Reports on the feasibility and effectiveness of translating proactive, antitumor necrosis factor (TNF) therapeutic drug monitoring (TDM) for inflammatory bowel disease into practice-wide quality improvement (QI) are lacking. We aimed to determine whether a TDM QI program improved outcomes at a large academic pediatric gastroenterology practice. Methods: We instituted local anti-TNF TDM practice guidelines to proactively monitor and optimize drug levels (goal >5 μg/mL). We conducted a retrospective single-center cohort analysis of patient outcomes before (pre-TDM) and after (post-TDM) guideline institution and assessed the independent effect by multivariable regression. Primary outcome was sustained clinical remission (SCR22-52), defined as physician global assessment (PGA) of inactive from 22 to 52 weeks and off corticosteroids at 52 weeks. Results: We identified 108 pre-TDM and 206 post-TDM patients. The SCR22-52 was achieved in 42% of pre-TDM and 59% of post-TDM patients (risk difference, 17.6%; 95% CI, 5.4–29%; P = 0.004). The post-TDM group had an increased adjusted odds of achieving SCR22-52 (odds ratio, 2.03; 95% CI, 1.27–3.26; P = 0.003). The adjusted risk of developing high titer antidrug antibodies (ADAs) was lower in the post-TDM group (hazard ratio, 0.18; 95% CI, 0.09–0.35; P < 0.001). Although the risk of anti-TNF cessation for any reason was not significantly different, there was a lower adjusted risk of cessation related to any detectable ADA in the post-TDM group (hazard ratio, 0.45; 95% CI, 0.26–0.77; P = 0.003). Conclusions: A practice-wide proactive anti-TNF TDM QI program improved key clinical outcomes at our institution, including sustained clinical remission, incidence of high titer ADA, and anti-TNF cessation related to ADA.